A survey of Agromyzidae (Diptera) reared from leafmines on Long Island, New York; host associations, distribution data, and the description and host association of a new species - Scheffer, Sonja J; Lonsdale, Owen (Zootaxa, 2018)
Leafmining Agromyzidae (Diptera) are both common and widespread, yet little is known of the host associations and distribution of most species. Here we report on a multi-year study of agromyzid diversity on Long Island, New York. We reared 45 species and identified for the first time a host plant for Agromyza masculina Sehgal and a likely host plant for Ophiomyia carolinensis Spencer. Of the 45 species, 17 are new records for New York State, for which fewer than 40 agromyzid species had previously been known. A new agromyzid species was reared from blotch mines on black-eyed Susan, Rudbeckia sp. and an undetermined yellow garden composite, both in the Asteraceae; this species is described here.